The mother of all questions - Solnit, Rebecca (Haymarket Books, 2017)
Praise for Men Explain Things to Me: "It's a fraught time to be female in America (or should I say fraught-er), and Rebecca Solnit's Men Explain Things to Me is the most clarifying, soothing, and socially aware document I've read on the topic this year."--Lena Dunham, Wall Street Journal "The Antidote to Mansplaining."-The Stranger "Feminist, frequently funny, unflinchingly honest, and often scathing in its conclusions."-Salon In a timely and incisive follow-up to her national bestseller Men Explain Things to Me, Rebecca Solnit offers sharp commentary on women who refuse to be silenced, misogynistic violence, the fragile masculinity of the literary canon, the gender binary, the recent history of rape jokes, and much more. In characteristic style, Solnit mixes humor, keen analysis, and sharp insight in these eleven essays. Writer, historian, and activist Rebecca Solnit is the author of eighteen or so books on feminism, western and Indigenous history, popular power, social change and insurrection, wandering and walking, hope and disaster, including the books Men Explain Things to Me and Hope in the Dark, both also with Haymarket; a trilogy of atlases of American cities; The Faraway Nearby; A Paradise Built in Hell: The Extraordinary Communities that Arise in Disaster; A Field Guide to Getting Lost; Wanderlust: A History of Walking; and River of Shadows, Eadweard Muybridge and the Technological Wild West (for which she received a Guggenheim, the National Book Critics Circle Award in criticism, and the Lannan Literary Award). A product of the California public education system from kindergarten to graduate school, she is a columnist at Harper's and a regular contributor to the Guardian.